Contracting capability: A distillation of co-operative principles from business history to guide present day restructuring - Boyce, Gordon (School of Management Working Papers, 1994)
The article re-examines the present day restructuring of large-scale enterprise in the West from a new perspective derived from business history, ttansaction cost economics, and game theory. Creating inter-organizational networks and modifying intra-finn arrangements to give human capital more scope of exercising autonomous judgement involves formulating co-operative contracts. The idea of "contracting capability" is developed to show how economic actors in the past established presence in an incipient bargaining flow, forged bonds of trust with other parties, and designed contracts that could accommodate sequential modification. By exercising strong leadership and communicating skills, they forged an initial agreement that became a foundation for sustaining a long-term, multiple-period relationship. Knowledge of history can help today's business leaders to identify the principles of contracting and to develop guidelines for evoking and preserving co-operative conduct